2020
DOI: 10.1002/mus.26899
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal delivery of nusinersen in individuals with complicated spines

Abstract: Background The treatment of spinal muscular atrophy (SMA) with nusinersen requires intrathecal medication administration, which can be challenging in individuals with complicated spines. This retrospective case series reviews the nusinersen treatment experience at one academic medical center with children and adults with SMA and complicated spines. Methods Twenty medical records of individuals receiving nusinersen were reviewed and administration methods summarized and assessed. Results Ten children and 10 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
(13 reference statements)
0
10
1
Order By: Relevance
“…For patients with type 1 SMA, life‐threatening respiratory symptoms, often requiring the presence of a multi‐disciplinary care team at the time of treatment administration, frequent sedation, and radiation exposure could cause concern. Spinal complications may limit the ability for a patient to receive nusinersen, although recent research has indicated that individuals with complicated spines can receive nusinersen injections using fluoroscopic guidance 20 In our study, however, the route of administration was noted as the primary reason for not being able to receive nusinersen treatment among both adult and pediatric patients.…”
Section: Discussioncontrasting
confidence: 55%
“…For patients with type 1 SMA, life‐threatening respiratory symptoms, often requiring the presence of a multi‐disciplinary care team at the time of treatment administration, frequent sedation, and radiation exposure could cause concern. Spinal complications may limit the ability for a patient to receive nusinersen, although recent research has indicated that individuals with complicated spines can receive nusinersen injections using fluoroscopic guidance 20 In our study, however, the route of administration was noted as the primary reason for not being able to receive nusinersen treatment among both adult and pediatric patients.…”
Section: Discussioncontrasting
confidence: 55%
“…18 In patients with complicated spines, several centers have reported successful intrathecal access using radiologic guidance or reservoir placement. [19][20][21][22] We successfully performed conventional, palpation-guided lumbar puncture for the majority of injections in patients with complicated spines. In the remainder, all were successfully performed using fluoroscopy-guided interlaminar lumbar punctures.…”
Section: Discussionmentioning
confidence: 99%
“…Lakhotia et al [ 17 ] presented the successful, uncomplicated, off-label use of the Ommaya reservoir in a patient with SMA type 2 and concomitant scoliosis with spinal fusion. A recent retrospective cohort on intrathecal methods of nusinersen delivery in 1 institution reported that 22% of injections in patients with complicated spines were performed through Ommaya reservoirs placed in the lumbar region [ 18 ]. This cohort included both adults and children with SMA types 1–3.…”
Section: Discussionmentioning
confidence: 99%